EXPERIMENTAL STUDY OF CARBON MEDIA AND TEMPERATURE VARIATIONS IN THE PACK CARBURIZING PROCESS OF STAINLESS STEEL 316L ON MATERIAL STRUCTURE AND HARDNESS VALUE - Wilibald Vincentius Mae Wangge Willyxsilvester; Nereus Tugur Redationo; Bernardus Crisanto Putra Mbulu (Universitas Katolik Widya Karya Malang, 2025)
The need for metal materials in various industries and construction is increasing. Materials that are widely needed by industry, especially the use of current research for the manufacture of electrodes in the electrolysis process. Some of the mechanical properties that are highlighted in quality include strength and wear resistance of the material. To meet these needs, various engineering techniques such as surface coatings are carried out to improve its mechanical properties. One approach that has been introduced is to change the structure of the material using a mixture of natural carbon-based materials, such as coconut shells and Arabica coffee grounds. Coconut shells and Arabica coffee grounds can be processed into carbon through a pyrolysis process at a temperature of 1000°C. The carbon is used as a material for the pack carburizing process with various heating temperatures (700°C, 800°C, 900°C) and various types of coconut shell carbon and Arabica coffee grounds with a base material of 316L stainless steel and will later undergo a testing process that tests the microstructure and hardness. The results of the structural and hardness tests show changes in the structure of the specimen. The higher the temperature, the higher the carbon mass value and the hardness value. Coconut shell carbon specimens with a temperature of 900°C have an average of the highest hardness value of 318 HV and specimens with the lowest hardness value of 293 HV Arabica coffee grounds carbon specimens with a temperature of 700°C. The content of C, Cr, and Ni affects hardness, strength, and high temperature resistance.